Secret sharing scheme Circular Visual Cryptography for Color Images - Survey - Parmar, Sudhir; Degadwala, Sheshang D; Modi, Nimit (International Journal of Computer Sciences and Engineering, 2025)
Information Security ensures mathematical techniques and related aspects to provide for confidentiality, data security, entity authentication and data origin authentication. Visual cryptography is a new technique which provides information security using simple algorithm unlike the complex, computationally intensive algorithms used in other techniques like traditional cryptography. This technique allows visual information to be encrypted in such a way that their decryption can be performed by the Human Visual System (HVS), without any complex cryptographic algorithms. Circular Random Grids extends the functionality by hiding more data in circular grids to provide confidentiality and secrecy without risking suspicion of an intruder. The proposed scheme complies with the methodology of secret sharing scheme where secret information is divided into various shares in meaningless form and is further recovered on overlapping printed transparencies with the shared information on it. Each of them is then validated for authenticity. An attempt has been made to use circular rings to embed the secret information with certain angular rotation and validation of the individual cipher shared in order to avoid cheating. In this paper we are describe every methods of VCS and presented its comparative study using advantages and disadvantages